Europe and Central Asia Economic Update, May 2017 : Trade in Transition in Europe and Central Asia - World Bank (Washington, D.C., 2017)
Trade played a pivotal role during the transition of many. countries in Europe and Central Asia to market economies. It forced a more efficient use of resourced and supported adoption of new technologies. Going forward, trade will again be crucial as countries adjust to new specialization patterns in the world. The adjustment requires not merely tweaking of trade policies, but rather a rethinking of how labor markets and capital markets are organized.